Live microalgal cells modified by L‐cys/Au@carbon dots/bilirubin oxidase layers for enhanced oxygen reduction in a membrane‐less biofuel cell. Issue 2 (28th March 2022) - Qing, Sili; Wang, Lin‐Lin; Jiang, Li‐Ping; Wu, Xiaoge; Zhu, Jun‐Jie
Abstract: Electrochemical oxygen reduced reaction (ORR) is a critical element in clean energy development. Despite efforts to enhance gas transfer to the reaction interface, the low solubility of O2 molecules and slow diffusion rate in liquid electrolyte is still a significant challenge. Herein, we design an artificial outer membrane on microalgal cells, which consists of a carbon dots/bilirubin oxidase (CDs/BOD) ORR catalyst layer and a L‐cystine/Au nanoporous O2 supply layer. O2 generated by photosynthesis from microalgal cells then can be directly transported to the CDs/BOD catalytic interfaces, overcoming the sluggish gas transfer in the electrolyte. Thus, the cathode constructed by the fabricated microalgal cells realizes an ORR current density of 655.2 μA/cm 2 with fast ORR kinetics, which is 2.68 times higher than that of a BOD cathode fed with pure O2 . A membrane‐less glucose/O2 biofuel cell is further developed using the hybrid artificial cells as the cathode, and the power density is 2.39 times higher than that of a BOD cathode biofuel cell in O2 saturated solution. This biomimetic design supplies O2 directly to the carbon dots/BOD catalyst layer from the microalgae membrane through a nanoporous L‐cys/Au layer, providing an alternative solution for the transfer barrier of O2 in the electrolyte. Abstract : The low solubility and slow diffusion of O2 in electrolyte seriously hinder the power output of biofuel cells. L‐cys/Au and carbon dots/bilirubin oxidase layers are engineered on the live microalgal cells for in situ O2 supply, and the obtained ACB@algae cathode realizes enhanced oxygen reduced reaction performance, providing a facile and green biofuel cell cathode.